The relationship between metabolic syndrome and survival of patients with endometrial cancer: a meta-analysis - Deng, Feng; Chen, Yi; Wu, Ying; Tang, Yawen; Yi, Wangjun (Frontiers in Oncology, 2024)
BackgroundMetabolic syndrome (MetS) is associated with a high risk of endometrial cancer (EC). However, its impact on EC progression remains unclear. This meta-analysis examined the association between MetS and survival outcomes in EC patients.MethodsA comprehensive search of PubMed, EMBASE, and Web of Science databases up to May 22, 2024, was conducted. Two independent reviewers performed study selection, data extraction, and quality assessment. Hazard ratios (HRs) and 95% confidence intervals (CIs) were calculated using a random effects model.ResultsNine studies comprising 13,579 endometrial cancer (EC) patients were included. Among these, 2,896 patients (21.3%) had MetS at the time of enrollment. The follow-up durations ranged from 3.4 to 14.2 years. The results showed that EC patients with MetS at baseline demonstrated significantly poorer overall survival (HR = 1.57, 95% CI = 1.19–2.07, p = 0.002; I2 = 25%) and progression-free survival (HR = 1.33, 95% CI = 1.08–1.63, p = 0.007; I2 = 16%). A similar association was observed for cancer-specific survival (HR = 1.26, 95% CI = 1.10–1.44, p = 0.001; I2 = 0%). Subgroup analyses based on study characteristics showed consistent results across studies conducted in countries with different follow-up durations.ConclusionThis meta-analysis suggests that MetS is associated with poor survival outcomes in EC patients. Further prospective studies are required to validate our findings. Systematic review registrationPROSPERO, identifier CRD42024561654.